2002
DOI: 10.1016/s0002-9440(10)62578-3
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of c-FLIP in Hodgkin and Reed-Sternberg Cells

Abstract: Crosslinking of the transmembrane receptor CD95/ Fas leads to activation of a signaling cascade resulting in apoptosis. c-FLIP is a recently described protein that potently inhibitsCD95/Fas protein is a 45-kd transmembrane protein that belongs to the tumor necrosis factor superfamily type of receptors.1 Crosslinking of the receptor leads to the clustering of an oligomolecular signaling platform, termed death-inducing signaling complex (DISC) that consists of the death domain of the intracellular part of Fas, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 44 publications
4
71
1
1
Order By: Relevance
“…As inhibition of constitutive NF-kB activation is sufficient to trigger apoptosis of H-RS cells without stimulation of death receptor or cytotoxic agents, survival of H-RS cells appears to depend on a balance between anti-apoptotic and pro-apoptotic activities. In support of this notion, the present study confirmed the downregulation of c-FLIP and Bcl-xL, which are reported to be frequently expressed in H-RS cells upon blocking of NF-kB activity [21][22][23][24] (Figure 5c and d).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As inhibition of constitutive NF-kB activation is sufficient to trigger apoptosis of H-RS cells without stimulation of death receptor or cytotoxic agents, survival of H-RS cells appears to depend on a balance between anti-apoptotic and pro-apoptotic activities. In support of this notion, the present study confirmed the downregulation of c-FLIP and Bcl-xL, which are reported to be frequently expressed in H-RS cells upon blocking of NF-kB activity [21][22][23][24] (Figure 5c and d).…”
Section: Discussionsupporting
confidence: 89%
“…[21][22][23][24] Bcl-xL and c-FLIP antagonize mitochondrial and membranous caspase activities. 25 We next examined changes in their expression upon DHMEQ treatment by Northern blotting and immunohistochemistry.…”
Section: Dhmeq-induced Apoptosis Involves Activation Of Caspases 3 8mentioning
confidence: 99%
“…On the other hand, there is high constitutive expression of FLIP in Reed-Sternberg cells of Hodgkin's lymphomas; and some evidences suggest that it prevents FAS-induced apoptosis in these cells. 30,18 There are also evidences that FLIP may inhibit the extrinsic apoptotic pathway in carcinomas of the prostate, 17 the stomach, 19 and the urinary bladder, 20 and melanoma. 31 On the other hand, FLIP has also been shown to be expressed in ovarian cancer, 32 a gynecologic type of tumor very similar to endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many tumors are resistant to Fas-and TRAIL-induced cell death through different molecular mechanisms (Wright et al, 1994). Some produce decoy receptors (DcRs) (Roth et al, 2001) some, such as colon cancer cells, express FasL to perform the so-called 'tumor counterattack' (Hahne et al, 1996;O'Connel et al, 1996) Thomas et al, 2002). The caspase-8 inhibitor FLIP (FLICE-Inhibitory Protein) has a caspase-like domain, but it lacks amino-acid residues that are critical for caspase activity.…”
Section: Introductionmentioning
confidence: 99%